MONOKULTURALISME DALAM TAYANGAN WEB SERIES ANIMASI ANAK NUSSA - Tristi, Muhammad Alzaki; Gusbet, Rani Attiqah (Jurnal Media dan Komunikasi Indonesia, 2024)
The objective of this study is to demonstrate how the concepts of monoculturalism are evident in the Nussa children's web series animations. Employing a qualitative approach, the research employed qualitative content analysis by examining five specific episodes from the Nussa Official YouTube channel. The qualitative content analysis employed a semiotic approach to dissect both explicit and implicit meanings. The basis for the content of monoculturalism is drawn from the concepts outlined in "Golden Truth" found in the publication "The Danger of Monoculturalism in the XXI Century" and Indonesia's Broadcasting Law no. 32/2002, encompassing two articles: Article (2) and Article (36). These concepts encompass four key points: (1) The prevalence of a monotonous society; (2) Inadequate portrayal of tolerance; (3) Insufficient diversity; and (4) A lack of communicative interaction and representation through cultural symbols. The findings of this investigation reveal that the animated content of Nussa does not adequately showcase societal and cultural variety in each episode. The Nussa production team also fails to incorporate dialogues and symbols that reflect the rich cultural diversity within Indonesia. In summary, it can be deduced that the content of Nussa's animated web series should incorporate increased diversity in forthcoming episodes.